2023
DOI: 10.3390/ijms24109060
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Unified Approach in Autoimmune Fibrotic Signalling Pathways

Abstract: Autoimmunity is a chronic process resulting in inflammation, tissue damage, and subsequent tissue remodelling and organ fibrosis. In contrast to acute inflammatory reactions, pathogenic fibrosis typically results from the chronic inflammatory reactions characterizing autoimmune diseases. Despite having obvious aetiological and clinical outcome distinctions, most chronic autoimmune fibrotic disorders have in common a persistent and sustained production of growth factors, proteolytic enzymes, angiogenic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…A flourishing research field is focused on the evaluation of the pathways involved in the fibrotic process observed in the salivary glands (SGs) derived from Sjögren’s Syndrome (SS) patients. Fibrogenesis observed in SGs can be considered the end result of chronic, intense inflammatory reactions induced by a variety of stimuli in this autoimmune disease [ 7 , 8 , 58 , 59 ]. Pioneering studies aimed at correlating SS with a fibrotic evolution of the salivary glands were conducted over 10 years ago, demonstrating a significant association between stimulated salivary flow, the focus score, and fibrosis in a high number of SS biopsy specimens.…”
Section: Role Of Emp/emt In Organ Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…A flourishing research field is focused on the evaluation of the pathways involved in the fibrotic process observed in the salivary glands (SGs) derived from Sjögren’s Syndrome (SS) patients. Fibrogenesis observed in SGs can be considered the end result of chronic, intense inflammatory reactions induced by a variety of stimuli in this autoimmune disease [ 7 , 8 , 58 , 59 ]. Pioneering studies aimed at correlating SS with a fibrotic evolution of the salivary glands were conducted over 10 years ago, demonstrating a significant association between stimulated salivary flow, the focus score, and fibrosis in a high number of SS biopsy specimens.…”
Section: Role Of Emp/emt In Organ Fibrosismentioning
confidence: 99%
“…More recently, studies have demonstrated an exuberant upregulation of TGF-β1 in SS SGs, which induces the loss of epithelial features and the acquisition of mesenchymal features in SG epithelial cells via triggering of the EMT program through the TGF-β1/Smad/Snail signaling pathway [ 62 ]. Indeed, TGF-β1 seems to be able to regulate EMT through both main pathways: the canonical Smad-dependent and non-canonical Smad-independent signaling pathways [ 7 , 8 , 62 ].…”
Section: Role Of Emp/emt In Organ Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, growing evidence has highlighted that aberrant fibrosis is also a major pathological feature of many chronic autoimmune diseases, including scleroderma, rheumatoid arthritis (RA), Crohn’s disease, systemic lupus erythematosus (SLE), and Sjögren’s syndrome (SS) [ 6 , 7 ]. These fibrotic diseases have, in common, a persistent inflammatory stimulus based on lymphocyte-monocyte interactions that produce growth factors and fibrogenic cytokines, inducing the deposition of connective tissue components that progressively destroy the healthy tissue structure [ 6 , 7 ]. These data confirmed that cytokines drive the acute and chronic inflammatory responses that culminate in fibrosis activation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%